Response of Corn Varieties under Saturated Soil Culture and Temporary Flooding in Tidal Swamp - Maulana, Arlingga Ichwan; Ghulamahdi, Munif; Lubis, Iskandar (Journal of Tropical Crop Science, 2019)
Corn is one of the important food crops and feeds in the world. Conversion of agricultural land into non-agricultural land is one of the major causes of the decline in corn production. Saturated soil culture (SSC) is a cultivation technology that gives continuous irrigation and maintains water depth constantly and makes soil layer in saturated condition. This technology can prevent pyrite oxidation in the tidal swamp. This research aimed to study the effect of temporary fl ooding under saturated soil culture on the growth and productivity of corn. The research was conducted at Karya Bhakti village, Rantau Rasau, Tanjung Jabung Timur, Jambi Province, Indonesia. The experiment used a split plot design with three replications. The main plot is fl ooding condition, consisted of 1) saturated soil condition continuously, from planting until harvesting time (as control), and 2) saturated soil condition from 0 to 10 DAP (Days after Planting) + fl ooding from 11 to 13 DAP + saturated soil condition from 14 to 28 DAP + fl ooding from 29-31 DAP + saturated soil condition from 32 DAP until harvesting time. The subplot is corn variety, “Sukmaraga”, “Bisma”, “Pioneer 27”, and “Bima 20”. “Pioneer 27” had the highest productivity of 9.33 t.ha-1. Corn varieties with moderate tolerance to temporary fl ooding were “Sukmaraga” and “Bisma”, whereas “Pioneer 27” and “Bima 20” are sensitive to fl ooding.